Impact of peripheral angioplasty on wound oxygenation measured with near-infrared spectroscopy in patients with critical limb ischemia. (14th October 2021) - Foerster, R; Stern, M; Heinen, Y; Baasen, S; Sansone, R; Heiss, C; Kelm, M; Busch, H L
Abstract:  : Impact of peripheral angioplasty on wound oxygenation measured with near-infrared spectroscopy in patients with critical limb ischemia Abstract Background: Near-infrared Spectroscopy (NIRS) has been proposed as a promising noninvasive tool for the assessment of hemoglobin oxygen saturation (StO2) in complex wounds in patients with critical limb ischemia (CLI). Objective: Up today, NIRS measurements are undertaken at single points near the wound, but not in the wound. Methods: In this prospective, single center study, 34 patients with PAD Rutherford stage 4–6 were included. We analyzed StO2 maps in and around the wound at baseline one day before and one day after angioplasty using a NIRS camera; macrovascular function was assessed by Doppler ultrasound with spectral analysis including ankle-brachial index (ABI). Results: Baseline StO2 of the wound area was 63% (± 3.66 [SE]) and 34% in the wound (± 4.8 [SE]). After successful angioplasty, wound area StO2 significantly increased to 71% (± 3.09 [SE]; p<0.001) and wound StO2 increased even more pronounced to 42% (± 4, 77 [SE]; p<0.001). Likewise, ABI increased in the treated leg (before 0.74±0.03 [SE]; after 0.87±0.02 [SE]; p=0.008). Conclusion: This is the first study to assess oxygenation in the wound using a NIRS camera after peripheral angioplasty. NIRS monitoring of wound oxygenation in patients undergoing endovascular treatment is a promising tool to monitor tissue perfusion. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Department of Cardiology, Pulmonology, and Vascular Medicine, University Duesseldorf, Medical Faculty, Duesseldorf, Germany